A Computational Approach to Digital Chinese Painting and Calligraphy - Xu, Songhua; Lau, Francis C. M.; Pan, Yunhe; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2009)
"A Computational Approach to Digital Chinese Painting and Calligraphy" is a technical book on computer science and its applications in the arts. It focuses on Oriental digital arts, in particular Chinese arts and painting, offering a multi-disciplinary treatment from the angles of computer graphics, interactive techniques, human-computer interaction, and artificial intelligence. The book also discusses the unique difficulties and challenges of using the computer to produce Oriental arts, including research results by the authors and their lessons and engineering experiences behind these efforts. Songhua Xu is a computer scientist of Zhejiang University and Yale University, as well as an honorary researcher of the University of Hong Kong. Francis C.M. Lau is Professor at the University of Hong Kong where he leads the Systems Research Group in the Department of Computer Science. Yunhe Pan is Professor of Computer Science at Zhejiang University as well as Deputy President of Chinese Academy of Engineering.
Computer Science and Fine Arts -- Computer Science in Painting: A Brief Survey -- Computer Science in Paintings or Drawings -- Interactive Digital Painting and Calligraphy -- to Interactive Digital Chinese Painting and Calligraphy -- Basic Algorithmic Framework of a Virtual Hairy Paintbrush System -- Performance Enhanced Virtual Hairy Paintbrush System -- Pigment Component of an Advanced Virtual Hairy Paintbrush System -- Rendering Component of an Advanced Virtual Hairy Paintbrush System -- Automatic Generation of Artistic Chinese Calligraphy -- Principles of Automatic Generation of Artistic Chinese Calligraphy -- Two Perspectives on Automatic Generation of Artistic Chinese Calligraphy -- A Preliminary Attempt at Evaluating the Beauty of Chinese Calligraphy -- Animating Chinese Paintings -- Animating Chinese Paintings through Stroke-based Decomposition -- Perspectives -- Final Fantasies for Digital Painting and Calligraphy.
Keywords: Computer science; Arts; User interfaces (Computer systems).; Artificial intelligence; Computer graphics; Application software; Computer Science; Computer Appl. in Arts and Humanities; Computer Graphics; User Interfaces and Human Computer Interaction; Artificial Intelligence (incl. Robotics).; Arts; Electronic books